2007
DOI: 10.1038/sj.bjc.6604037
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of molecular markers (p53, EGFR, ATM, CHK2) in multimodally treated squamous cell carcinoma of the oesophagus

Abstract: Pretherapeutic identification of oesophageal squamous cell carcinomas that will respond to neoadjuvant chemoradiotherapy is an important attempt for improvement of patient's prognosis. In the current study, pretherapeutic biopsies from 94 oesophageal squamous cell carcinomas (cT3, cN0/ þ , cM0) in patients who underwent neoadjuvant chemoradiotherapy (RCTx: 45 Gy plus cisplatin and 5-fluorouracil) and subsequent oesophagectomy in the setting of a single-centre prospective treatment trial were investigated by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 25 publications
1
25
0
1
Order By: Relevance
“…Thus, assessment of the overexpression and accumulation of mutant p53 protein by immunohistochemistry has been widely used to detect abnormal p53 expression in cancers. Although several studies have examined the relationship between p53 IHC expression and prognosis in ESCC, this work is limited by the small sample size, and the results are controversial [7][8][9][10][16][17][18][19][20][21][22]. We conducted a large-scale study with a long follow-up to examine p53 expression in relation to the clinicopathologic features and prognosis of ESCC.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, assessment of the overexpression and accumulation of mutant p53 protein by immunohistochemistry has been widely used to detect abnormal p53 expression in cancers. Although several studies have examined the relationship between p53 IHC expression and prognosis in ESCC, this work is limited by the small sample size, and the results are controversial [7][8][9][10][16][17][18][19][20][21][22]. We conducted a large-scale study with a long follow-up to examine p53 expression in relation to the clinicopathologic features and prognosis of ESCC.…”
Section: Discussionmentioning
confidence: 97%
“…In ovarian cancer, although ATM and Chk2 protein expressions were not found to be individually related to overall survival, at least one alteration was found to be a negative predictor of overall survival [19]. On the other hand, the expressions of ATM and Chk2 were not found to have predictive value in multimodality-treated esophageal squamous cell carcinoma [20]. With regard to gastric cancer, it has been reported that the presence of a low level of phosphorylated ATM is significantly correlated with poor differentiation, lymph node metastasis, and poor 5-year survival [21].…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor receptor is often overexpressed in patients with oesophageal cancer, suggesting an important role for it in the development of this disease (Sarbia et al, 2007;Wang et al, 2007;Wei et al, 2007). All Kyse cell lines were found to express EGFRs, whereas HER2 was expressed only in Kyse410 (data not shown).…”
Section: -Aag Inhibits Pro-survival Signalling Pathwaysmentioning
confidence: 99%